Peran Dukungan Sosial Keluarga, Atasan, dan Rekan Kerja terhadap Resilient Self-Efficacy Guru Sekolah Luar Biasa - Elisabeth Santoso; Jenny Lukito Setiawan (Jurnal Psikologi, 2018)
This study aimed to investigate the influence of social support from family, supervisor, and co-workers toward the resilient self-efficacy of SEN teachers in Surabaya. This study involved 94 SEN teachers from Special Educational Needs school in Surabaya. The study used social support measures and resilient self-efficacy scale. Multiple regression analysis showed that social support from family, supervisor, and co-workers significantly influenced SEN teachers’ resilient self-efficacy (F = 28,052; p<0,05). These supports gave an effective contribution to resilient self-efficacy as much as 48,3% (R²=0,483). Hypothesis testing also showed that each source of support significantly influenced SEN teachers’ resilient self-efficacy. Therefore, social support from family, supervisors, and co-workers influenced the resilient self-efficacy of SEN teachers, whether they are given simultaneously or separately.